The Effect Of Coagulation Bath Temperature On The Mechanical Properties Of PAN-Based Carbon Fiber - Rahman, M. A.; Ismail, A. F.; Mustafa, A.; Ng, B. C.; Hasbullah, H.; Rahaman, M. S. A.; Abdullah, M. S. (2004)
The objective of this research is to produce and characterize PAN fibers in order to produce high performance carbon fibers. The PAN fiber was produced using a simple dry - wet spinning process where the polymer solution was extruded through an air gap following by coagulation process. The formation of PAN fiber was controlled by coagulation temperature inside the bath and the jet stretch. Low coagulation bath temperature was responsible to retard the coagulation rate and controlling the diffision of solvent and non-solvent inside and at the surface of the PAN fiber. Stretching was applied to the as-spun fiber in order to align the molecular chain along the axis thus increases the crystallinity of PAN fiber and to help in raising the Young's modulus. The crystallinity of PAN fiber was determined using X-ray diffraction. The mechanical properties of PAN fiber such as Young's modulus and tensile strength were examined in order to investigate the effect of coagulation bath temperature and jet stretch. The PAN fiber produced at a 15 C coagulation bath and 3 jet stretches exhibited the highest tensile strength and Young's Modulus of 0.96 GPa and 5.21 GPa respectively.